Seaward : a novel - Leithauser, Brad. (New York : Knopf, 1993)
Part social comedy, part ghost story, part psychological drama about the nature of friendship and love.
Booklist.
Library Journal Starred.
New York Times.
Adult
Keywords: Bereavement -- Fiction; Psychological fiction